The Simulation Model of Iron Sponge Plant Layout for the Defense Industry Based on Industry 4.0 Model - Sovian Aritonang; Riyadi Juhana (STKIP Singkawang, 2020)
The Industry 4.0 is a change in the perspective of how to view an industry based on the resources owned, to operate according to needs. The sponge iron industry is a raw material industry to support the steel industry which is intended as material for shipbuilding and combat vehicles used by the Indonesian National Millitary. It is necessary to plan and design a sponge iron plant with an Industrial 4.0 model. The implementation of the Industry 4.0 model aims to optimize the operational needs of the plant, especially the sponge iron plant, which is relatively rare in Indonesia. The concept of a factory layout (cellular layout, modular layout), the concept of lean manufacturing, as well as the concepts and principles of the smart factory (Cyber-Physical Systems) are concepts that will be applied in the planning and design of the Industrial 4.0 sponge iron plant layout. In order to produce an optimal layout, a simulation model using FlexSim 2018 Software and layout optimization is used the Computerized Relative Allocation of Facilities Technique (CRAFT) algorithm with the help of CRAFT Software Integrated Microsoft Excel 2019.